Learning About Failure: Bankruptcy, Firm Age, and the Resource-Based View - Thornhill, Stewart; Amit, Raphael (Organization Science, 2003)
Systematic differences in the determinants of firm failure between firms that fail early in their life and those that fail after having successfully negotiated the early liabilities of newness and adolescence are identified. Analysis of data from 339 Canadian corporate bankruptcies suggests that failure among younger firms may be attributable to deficiencies in managerial knowledge and financial management abilities. Failure among older firms, on the other hand, may be attributable to an inability to adapt to environmental change.